Scope of Selective Heterocycles From Organic and Pharmaceutical Perspective 2016
DOI: 10.5772/64050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitriles – Synthesis of 4-Cyano Pyrazole, 5-Aminopyrazole Derivatives and the Deamination of 5-Aminopyrazole Derivatives

Abstract: Chemoselective reaction on 3-dimethylamino-2-aroyl-propenenitrile and hydrazine in acidic medium yields 4-cyano pyrazole, where as in basic medium yields 5-amino pyrazoles as major product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…19,20 As a phenylbutazone derivative, feprazone has a similar structure to phenylbutazone, with the main difference lying in the replacement of the butyl located at the C4 position on the pyrazoline-2,5-dione skeleton with a 3-methylbutenyl substituent. 21 Feprazone and other members of the pyrazolone family have been used for decades owing to their wide range of pharmacological activities, including antipyretic, analgesic, anti-inflammatory, antioxidant, anticancer, and many others. 22−24 In the present study, we investigated whether feprazone might mitigate the effects of FFA in human aortic endothelial cells (HAECs) and explored the underlying mechanism.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 As a phenylbutazone derivative, feprazone has a similar structure to phenylbutazone, with the main difference lying in the replacement of the butyl located at the C4 position on the pyrazoline-2,5-dione skeleton with a 3-methylbutenyl substituent. 21 Feprazone and other members of the pyrazolone family have been used for decades owing to their wide range of pharmacological activities, including antipyretic, analgesic, anti-inflammatory, antioxidant, anticancer, and many others. 22−24 In the present study, we investigated whether feprazone might mitigate the effects of FFA in human aortic endothelial cells (HAECs) and explored the underlying mechanism.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Prostaglandins are a type of fatty acid that trigger pain and inflammation and have been shown to contribute to atherosclerotic plaque rupture by mediating the expression of MMPs . Previous research has demonstrated the involvement of COX-2-mediated prostaglandin production in the pathological mechanism of AS. , As a phenylbutazone derivative, feprazone has a similar structure to phenylbutazone, with the main difference lying in the replacement of the butyl located at the C4 position on the pyrazoline-2,5-dione skeleton with a 3-methylbutenyl substituent . Feprazone and other members of the pyrazolone family have been used for decades owing to their wide range of pharmacological activities, including antipyretic, analgesic, anti-inflammatory, antioxidant, anticancer, and many others. In the present study, we investigated whether feprazone might mitigate the effects of FFA in human aortic endothelial cells (HAECs) and explored the underlying mechanism.…”
Section: Introductionmentioning
confidence: 99%